(Cholesterol content of various Animal-based snacks from west java) - Sait, Salya; Satyaputra, Inggriani; F.Hutajulu, Tiurlan; D. Darlianti, Neneng (Warta Industri Hasil Pertanian, 1994)
To increase the costumer acceptance and provide a safeguard of the animal-based snacks customers against the consumption of excessive cholesterol, the quantitative data on the level of cholesterol content of some animal-based sancks produced in west java,i.e. chips of sliced fried chiken small intestine,floured fried eel and cow lung :seasoned dried eel and side-dish of GLC analysis using pracedures for both the formation of acetate derivatives and those of TMS derivatives. Meanwhile,the moistures content as wes as the total fast were also determined.The result of analysis indicated that the highest content of cholesterol was about 3,26. Where as the lowest was about 0.009 grams/100 grams of the food sample, while the level cholesterol content did not depend on the levels of total fast contents.